2017
DOI: 10.1039/c6ta10749d
|View full text |Cite
|
Sign up to set email alerts
|

Multimetallic Ni–Mo/Cu nanowires as nonprecious and efficient full water splitting catalyst

Abstract: Multimetallic Ni–Mo/Cu nanowires free-standing electrode (NM-CNW) was used as an excellent bifunctional electrocatalyst for full water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 42 publications
6
56
0
Order By: Relevance
“…However, although some previous works have shown that Ni−Mo is unstable in alkaline media, the origins of this instability have not been extensively studied to date, aside from one key work by Schalenbach et al., who reported that Ni−Mo can form multiple crystal phases depending on the ratio between Ni and Mo. Furthermore, they reported that Mo can leach from the material during electrocatalysis …”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, although some previous works have shown that Ni−Mo is unstable in alkaline media, the origins of this instability have not been extensively studied to date, aside from one key work by Schalenbach et al., who reported that Ni−Mo can form multiple crystal phases depending on the ratio between Ni and Mo. Furthermore, they reported that Mo can leach from the material during electrocatalysis …”
Section: Introductionmentioning
confidence: 84%
“…Amongst these materials, one of the most promising ones is alloyed Ni−Mo, which is surmised to have a hydrogen bonding energy (HBE) similar to that of Pt, owing to the synergy between Ni and Mo in alkaline water splitting . Alkaline water splitting is considered because of its relevance in industry and the availability of better‐performing anodes in alkaline relative to acidic media …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Se 3d region ( Figure 4D), the peaks at 54.3 and 58.6 eV correspond to Se 3d 5/2 and SeO x (Se species with a high oxide state), respectively. [52,53] Together with the result of XRD pattern shown in Figure S2 in the Supporting Information, the peaks at 932.4 and 952.0 eV can be assigned to metallic Cu 0 . The peak at 531.4 eV can be ascribed to the oxygen in oxyhydroxide (OOH), which indicates that some of Ni and Co in the surface of Ni 0.35 Co 0.65 Se 2 /CNW exist in the form of oxidation states such as γ-NiOOH and γ-CoOOH.…”
Section: Introductionmentioning
confidence: 63%
“…After electrochemical anodization of pure copper foam at a constant current density of 10 mA cm −2 for 30 minutes and then as‐anodized nanowire thermal annealing at 180 °C for 1 h to form CuO NWs and the corresponding XRD pattern is shown in Figure (b) displays multiple diffraction peaks at 32.5°, 35.5°, 38.9°, 48.8°, 53.5°, 58.3°, 66.1°and 68.0°, which are attributed to (110), (002), (111), (−202), (020), (202), (310), and (220) crystal planes of CuO (JCPDS No. 080‐1916) . Furthermore, the in‐situ growth of Co‐MOF on the surface of CuO NWs and followed by pyrolysis of CuO NWs@Co MOF at 350 °C for 3 h at air atmosphere, and is examined by XRD diffraction pattern as shown in Figure (c).…”
Section: Resultsmentioning
confidence: 99%